Pembentukan Kosakata Baru Sebagai Bentuk Coinage dalam Media Sosial Instagram - Kartika Tiara Syarifuddin; Abdul Hafid (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2018)
This study aimed to describe the process of forming a new vocabulary as a form of coinage in the hashtag from the point of view of the adoption process and adaptation processes that existed on social media, especially Instagram, which currently became one of the most active social media used by Indonesian teens. The method used in this study was a qualitative descriptive method. The data collection technique used was the note taking technique, while the data analysis technique used was the data analysis technique by Miles and Huberman (interactive models) which was started from the data collection stage, data reduction, data presentation (data display), and verification or conclusion (conclusion drawing). Determination of the process of forming a new vocabulary was based on the word formation process. Based on the results of the study, it was found that 14 data experienced the adoption process, and 6 data that experienced an adaptation process. Conclusion, on Social media Instagram which was focused on the hashtag used as a coinage form showed that the number of new vocabulary formation from the adoption process was divided into seven types of adoption forms, meanings and purposes of use, (1) single + two double vowels, (2) double vowels+ two words, (3) double vowels + three words, (4) two words, (5) three words, (6) acronyms, (7) whole words + word loss, while the adaptation process was divided into two types of meaning adaptations, words and class words namely, (1) KVK and KVKV, (2) KKVK + word dissolution. Keywords: Coinage, Social Media, Instagram.